Pedro Azara (ed.), "Antes del diluvio. Mesopotamia 3500-2100 A.C." - Espejel Arroyo, Fernando (Gerión. Revista de Historia Antigua, 2015)
Pedro Azara (ed.), Antes del diluvio. Mesopotamia 3500-2100 A.C.,